Maqashid Syariah Perspektif Izzudin Abdi Salam - Moh. Alfin Sulihkhodin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
The rapid development of legal problems in the paradigm of human life requires scholars and jurists to always try to find the basic rules of Islamic Law, the order to make a renewal and new adjustment to the needs of the times which are always evolving from time to time. No doubt if the jurists are like Imams al-Ghazali, al-Juwaini, as-Syatibhi, Najmuddin at-Thufi, Izzudin Abdi Salam, Khalid Abu el-Fadhl, Muhammad Syahrur, as well as other scholars continue to strive to carry out Ijtihad, in the field of Maqashid Sharia in Particular. This qualitative research using the literature study approach seeks to explore the concept of maqashid sharia gradation which was coined by Sheikh Izzudin Abdi Salam. Where according to the idea it can be understood that, all forms of Sharia are made as an effort to bring benefit and reject mafsadat. Whether worldly or ukhrawi. It can also be understood that, this maqashid gradation is more emphasized on everything that is haqiqi and majazi in nature. Don’t be emphasizing the aspects of Dharuri, Hajj, or Tahsini. So, that in the end everything is done with hope (strong suspicion) not in certainty of all forms of mukallaf deeds.